Legal Review of The Criminal Act of Defamation Through Writing - Frengki Yulianto; Bastianto Nugroho; Sri Anggraini K. Dewi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The aim of the research is to determine the application of the law to criminal acts of defamation through writing. The research method is normative research, with a conceptual approach, namely legal research that looks for principles, doctrines and sources of law in a juridical philosophical sense. The basic results of the judge's legal considerations in deciding criminal defamation cases. There are proven facts in the elements of Article 311 paragraph (1) of the Criminal Code, in this case the crime of defamation. There is evidence based on valid evidence as regulated in Article 184 of the Criminal Procedure Code which is proven at trial. Factors that mitigate and aggravate the defendant.